Intermediating organisations in regional innovation systems:high-technology enterprise survey from Northern Finland - Suorsa, Katri (Georgia Institute of Technology, 2008)
Proceedings of the 5th International Ph.D. School on Innovation and Economic Development, Globelics Academy 2008, Tampere, 2nd of June 13th of June, 2008.